[Psyche] - Bell, Andrew (My University, 2010)
The underlying assumption is that your immediate built and natural environment has an effect on your psyche and your mental well-being. This paper is about formulating a conceptual framework and a set of recommendations that could inform the design process around creating spaces for well-being both mentally and physically, ultimately pertaining to the planning of a contemporary psychiatric facility. This will be done through a review of current literature on environmental psychology, architecture and evidence-based design, together with an historical review of space used and created for the treatment and housing of people with mental illness both locally and internationally. Numerous interviews with professionals in both architectural and psychiatric fields will reinforce the evidencebased design approach of this thesis. A precedent study of architecture pertaining to well-being and deinstitutionalisation will also contribute to the understanding that architecture has an integral role to play in the creation of space that is conducive to recovery from mental illness. It has been discovered that very few concrete guidelines exist for producing spaces for mental well-being, yet there is a vast body of research that proves that our environment has an affect on our cognitions and ultimately our well-being, especially in hospital and psychiatric settings. It is my hope that, through an evidence-based design approach, an appropriate, holistic, and sustainable solution for the creation of space for wellbeing in a psychiatric situation can be achieved